2016
DOI: 10.4103/1357-6283.188726
|View full text |Cite
|
Sign up to set email alerts
|

Teaching tobacco cessation to large student cohorts through train-the-trainers and problem based learning strategies

Abstract: Educational intervention based on a train-the-trainers and problem-based learning approaches are feasible and effective to educate a large cohort of first-year medical students in tobacco issues. Further research is needed to find out whether this intervention improves overall patient care management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Patient empowerment can strengthen capacity for self-management and improve treatment outcomes. 21 In this study, we showed that the empowerment model of PBL health education could effectively improve the self-management knowledge, skills, anxiety, depression, and quality of life of PD patients. In addition, PBL health education significantly improved PD patients' satisfaction with the hospital.…”
Section: Discussion and Conclusion Discussionmentioning
confidence: 73%
“…Patient empowerment can strengthen capacity for self-management and improve treatment outcomes. 21 In this study, we showed that the empowerment model of PBL health education could effectively improve the self-management knowledge, skills, anxiety, depression, and quality of life of PD patients. In addition, PBL health education significantly improved PD patients' satisfaction with the hospital.…”
Section: Discussion and Conclusion Discussionmentioning
confidence: 73%